Tax Aggressiveness, Fair Value Accounting, Debt Maturity: Does Integrated Reporting Matter? - Pria Aji Pamungkas; Amrie Firmansyah; Resi Ariyasa Qadri; Agung Dinarjito; ZefArfiansyah (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2022)
This study investigates the association between tax aggressiveness, fair value accounting and debt maturity and whether Integrated Reporting (IR) moderates those relationships. This study's methodology is a quantitative approach with multiple linear regression models and panel data. The sample employed in this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX). The type of data used is secondary data sourced from financial statements and annual reports from 2016 to 2020. The sample selection using a purposive sampling method with the number of samples amounted to 595 firm-year observations. This study suggests that tax aggressiveness and fair value accounting have an inverse association with debt maturity. However, IR failed to weaken the negative impact of extensive fair value accounting on debt maturity. The Financial Services Authority (OJK) can consider this study to improve supervision and regulation for better creditor protection through the company's optimal debt maturity policy.